Patient-reported outcomes in the single-tablet regimen (STaR) trial of rilpivirine/emtricitabine/tenofovir disoproxil fumarate versus efavirenz/emtricitabine/tenofovir disoproxil fumarate in antiretroviral treatment-naive adults infected with HIV-1 through 48 weeks of treatment. Issue 3 (3rd March 2016) - Wilkins, Ed L.; Cohen, Calvin J.; Trottier, Benoit; Esser, Stefan; Smith, Don E.; Haas, Bernhard; Brinson, Cynthia; Garner, Will; Chuck, Susan; Thorpe, David; De-Oertel, Shampa
ABSTRACT: This 96-week, randomized, open-label study was designed to assess the efficacy and safety of two single-tablet regimens in treatment naïve HIV-1-infected adults: rilpivirine (RPV) + emtricitabine/tenofovir disoproxil fumarate (FTC/TDF) and efavirenz (EFV) + FTC/TDF. Assessments included patient-reported Medication Adherence Self-Report Inventory, SF-12v2 Quality of Life assessment, HIV Treatment Satisfaction Questionnaire, and HIV Symptom Index Questionnaire through Week 48. Additional evaluations included study drug discontinuations due to treatment-emergent adverse events (TEAEs). A total of 786 participants (n=394 RPV/FTC/TDF, n=392 EFV/FTC/TDF) were included. Fewer RPV/FTC/TDF-treated than EFV/FTC/TDF-treated participants discontinued study drug due to TEAEs (2.5% vs. 8.7%), with 41% (14/34) TEAE-related discontinuations in the EFV/FTC/TDF group occurring within the first four weeks of treatment. Treatment adherence and satisfaction remained high through Week 48 and quality of life improved from baseline in both groups. There were no significant between-group differences in virologic success (HIV-1 RNA <50 copies/mL) regardless of adherence (<95% or ≥95%). Significant between-group differences favouring RPV/FTC/TDF were observed for the HIV SIQ symptoms of difficulty falling or staying asleep (p = .022) and diarrhea or loose bowel movements (p = .002). In conclusion, 48-week treatment with RPV/FTC/TDF or EFV/FTC/TDF was associated with high adherence, high treatment satisfaction, and improved quality of life. TEAE-related discontinuations and patient-reported symptoms indicate that RPV/FTC/TDF may be somewhat better tolerated than EFV/FTC/TDF.